2019
DOI: 10.1016/j.scitotenv.2019.06.441
|View full text |Cite
|
Sign up to set email alerts
|

Impact of biochar application dose on soil microbial communities associated with rubber trees in North East Thailand

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 61 publications
0
19
0
3
Order By: Relevance
“…Herrman et al (2019) concluded that the addition of biochar from rubber tree caused a raise of the soil pH value as well as its nutrient content. In the research cited higher sensitivity to the activity of applied biochar was recorded in the case of fungi occurring in the soil as compared to bacteria present there [38]. Similar studies were performed in Bulgaria [39] using biochar in the cultivation of wheat and maize in crop rotation.…”
Section: Discussionmentioning
confidence: 62%
“…Herrman et al (2019) concluded that the addition of biochar from rubber tree caused a raise of the soil pH value as well as its nutrient content. In the research cited higher sensitivity to the activity of applied biochar was recorded in the case of fungi occurring in the soil as compared to bacteria present there [38]. Similar studies were performed in Bulgaria [39] using biochar in the cultivation of wheat and maize in crop rotation.…”
Section: Discussionmentioning
confidence: 62%
“…Increases in the soil microbial biomass and respiration owing to the addition of biochar can be explained by the following factors: (1) increased soil SOC (Fig. 2) and supplemented labile carbon and soluble nutrients for microbial utilization (Xu et al 2018;Herrmann et al 2019); (2) reduced soil Cd availability (Fig. 3) and mobility ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Esta morfologia em folhas já é bem conhecida destes materiais obtidos de reagentes comerciais (Figueira et. al, 2008;Zhang et al, 2014;CUI et al, 2009 O biocarvão produzido a partir de resíduos de culturas agrícolas vem sendo utilizado em larga escala para melhoria da qualidade física e química dos solos (LEHMANN et al, 2011) e diversos estudos tem avaliado as contribuições deste material para biota edáfi ca (CHINTALA et al, 2016;ANDRÉS et al, 2019;HARDY et al, 2019;HERRMANN et al, 2019;PALANSOORIYA et al, 2019).…”
Section: Materiais E Métodounclassified